Artificial Intelligence / Second Edition - Knight Kevin; Rich Elaine (Mcgraw Hill, Inc, 1991)
International Edition. Preface, Problems and Search, What Is Artificial Intelligence, Problems and Problem Spaces and Search, Heuristic Search Techniques, Knowledge Representation, Using Predicate Logic, Representing Knowledge Using Rules, Symbolic Reasoning Under Uncertainty, Statistical Reasoning, Strong Slot-and-Filler Structures, Advanced Topics, Game Playing, Planning, Understanding, Natural Language Processing, Learning, Connectionist Models, Common Sense, Expert Systems, Perception and Action, Conclusion, References, Acknowledgements, Index.